2020
DOI: 10.3390/nu12092594
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Changes over Time of Lipid Profile, C-Reactive Protein Level and Body Mass Index in Teenagers and Young Adults on Different Diets Belonging to Autism Spectrum Disorder

Abstract: Background: Numerous scientific studies on patients with autism spectrum disorder (ASD) suggest a significant role of inflammation processes or lipid disorders in this spectrum of neurodevelopmental disorders. Unfortunately, there is a lack of assessments of changes over time regarding level of lipids and inflammatory markers in people diagnosed with ASD using different diets. The aim of this study was to evaluate changes in lipid profile, high sensitivity C-reactive protein (hs-CRP) and body mass index (BMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…In contrast with the mentioned results, a study conducted by Blazewicz and collaborators showed an increase of TC levels in adolescents with autism, divided into groups according to dietary characteristics [ 33 ]. In particular, the presence of increased TC/high-density lipoprotein (HDL) plasma levels was found in patients with ASDs compared to healthy controls regardless of the type of diet.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In contrast with the mentioned results, a study conducted by Blazewicz and collaborators showed an increase of TC levels in adolescents with autism, divided into groups according to dietary characteristics [ 33 ]. In particular, the presence of increased TC/high-density lipoprotein (HDL) plasma levels was found in patients with ASDs compared to healthy controls regardless of the type of diet.…”
Section: Resultsmentioning
confidence: 82%
“…In particular, the presence of increased TC/high-density lipoprotein (HDL) plasma levels was found in patients with ASDs compared to healthy controls regardless of the type of diet. In addition, the groups of patients characterized by low-fat diet or regular diet showed an increase in triglycerides (TG), while the group of patients following a gluten-casein-free diet exhibited an increase in non-HDL cholesterol [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity or overweight is typically the first stimulus prompting dietary intervention, and many individuals with autism are on various specific diets (e.g., a gluten-free, casein-free or low-fat diet) [ 49 ], and thus a thorough analysis of selenium status in relation to nutrition and diets could complement our future research. Lifestyle factors affecting choice of diet and physical activity, as well as the type of pharmacological treatment, are issues for further study that may help to determine whether Se imbalance is mainly due to altered metabolic processes, insufficient dietary intake, or both.…”
Section: Discussionmentioning
confidence: 99%